1982
DOI: 10.1007/bf02411267
|View full text |Cite
|
Sign up to set email alerts
|

Cytology and autoradiography of estrogen-induced differentiation of avian endosteal cells

Abstract: The endosteal reaction, the initial step in the formation of medullary bone, was investigated in femurs of estrogen-treated male Japanese quail. Morphologically, the endosteal cells were in an undifferentiated state until 30 h after estrogen treatment and showed characteristics resembling those of resting cells. Many preosteoblasts were seen on the endosteum at 33 h, whereas mitotic figures and fully differentiated osteoblasts were recognized at 36 h after estrogen. The mitotic figures were observed among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Kinetic study would be needed to rule out this possibility. Our findings, nevertheless, are consistent with: 1) the demonstration of the uptake of radiolabeled estrogen in the bone marrow along the endosteum in mice (Budy, 1962) and of the induction of endosteal cell differentiation with a subsequent increase in osteoblast formation in quail (Kusuhara and Schraer, 1982;Bowman and Miller, 19861, suggesting the site of hormone action; 2) a short-term autoradiographic study showing a n increased number of metaphyseal osteoblasts labeled with 3H-thymidine in mice 24 hours after estrogen treatment (Simmons, 1963); 3) observations of increased 3H-thymidine incorporation or cell proliferation in cultures of osteoblastic cells (Vaishnav et al, 1984;Ernst et al, 1988Ernst et al, , 1989 and increased proliferation of osteogenic cells in cultures of fetal long bones (Liskova-Kiar, 1978) after estrogen treatment; and 4) a recent report of direct stimulation of bone formation in ovariectomized rats given estrogen locally (Takano-Yamamoto and Rodan, 1990). It has been suggested, based on gross histological observations, that the increase in bone mass seen in tibia andlor femoral shafts of estrogen-treated mice is due to the extension of unresorbed metaphyseal trabecular bone into the diaphysis Silberberg, 1941a, b, 1971;Urist et al, 1950).…”
Section: Discussionsupporting
confidence: 92%
“…Kinetic study would be needed to rule out this possibility. Our findings, nevertheless, are consistent with: 1) the demonstration of the uptake of radiolabeled estrogen in the bone marrow along the endosteum in mice (Budy, 1962) and of the induction of endosteal cell differentiation with a subsequent increase in osteoblast formation in quail (Kusuhara and Schraer, 1982;Bowman and Miller, 19861, suggesting the site of hormone action; 2) a short-term autoradiographic study showing a n increased number of metaphyseal osteoblasts labeled with 3H-thymidine in mice 24 hours after estrogen treatment (Simmons, 1963); 3) observations of increased 3H-thymidine incorporation or cell proliferation in cultures of osteoblastic cells (Vaishnav et al, 1984;Ernst et al, 1988Ernst et al, , 1989 and increased proliferation of osteogenic cells in cultures of fetal long bones (Liskova-Kiar, 1978) after estrogen treatment; and 4) a recent report of direct stimulation of bone formation in ovariectomized rats given estrogen locally (Takano-Yamamoto and Rodan, 1990). It has been suggested, based on gross histological observations, that the increase in bone mass seen in tibia andlor femoral shafts of estrogen-treated mice is due to the extension of unresorbed metaphyseal trabecular bone into the diaphysis Silberberg, 1941a, b, 1971;Urist et al, 1950).…”
Section: Discussionsupporting
confidence: 92%
“…A major unanswered question is whether estrogen action on bone in vivo is direct or indirect (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). It has been suggested that in vivo estrogen promotes the systemic production of growth factors, so-called estromedins, or the removal of growth inhibitors, estrocolyons, elsewhere in the body (42).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of E on bone is uncertain despite studies over the past three decades reporting effects on bone in rodents and quail and on mineral metabolism in humans (1)(2)(3)(4)(5)(20)(21)(22)(23)(24)(25)(26)(27)(28). The studies in rodents and quail have found effects of exogenous estrogens on osteoblasts, their precursors, or both (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The studies in rodents and quail have found effects of exogenous estrogens on osteoblasts, their precursors, or both (20)(21)(22)(23)(24)(25)(26)(27)(28). Endosteal proliferation and metaphyseal sclerosis were observed in several studies, implying an anatomic localization of the estrogen effect.…”
Section: Discussionmentioning
confidence: 99%